Efficacy and safety of the 9-mm intrabronchial valve in patients with advanced emphysema - Kontogianni, Konstantina; Gompelmann, Daniela; Valipour, Arschang; Gerovasili, Vasiliki; Schuhmann, Maren; Stanzel, Franz; Herth, Felix; Eberhardt, Ralf (Respiration, 2020)
Background: Endoscopic valve therapy aims at lung volume reduction that is associated with improved lung function, exercise tolerance and quality of life in emphysema patients. The size of intrabronchial valves of the Spiration® Valve System (SVS) selected to achieve lobar occlusion may have an influence on treatment outcomes. Methods: 49 severe emphysema patients (M/F: 24/25, age: 64 ± 7 years), with complete interlobar fissures on the side intended to be treated, underwent treatment with at least one 9-mm intrabronchial valve implantation at 3 centers and were followed up at 30, 90 and 180 days after intervention. Changes in pulmonary function tests (PFT), 6-min walk test (6MWT), modified Medical Research Council (mMRC) dyspnea scale and chronic obstructive pulmonary disease assessment test scores as well as possible complications were recorded. Results: Forced expiratory volume in 1 s (FEV1) improved significantly over the 6-month period of the study, and the proportion of patients achieving a minimal clinically important difference (MCID) for FEV1 was 46.4% at 6 months. Regarding the remaining PFT values, the changes were not statistically significant at 6 months, but when looking at the MCIDs, 44.4% of the patients achieved the MCID decrease for residual volume. The 6MWT distance also improved statistically significantly, and an MCID increase of ≥26 m was reached by 41.7% of the patients. Furthermore, there was a statistically significant improvement in the mMRC score. The incidence of pneumothoraxes requiring drainage was 26.5% while a valve dislocation rate of 24% was observed but only in the lower lobes. Conclusions: Endoscopic lung volume reduction with the 9-mm SVS valves was associated with statistically significant but modest improvement of FEV1, mMRC and 6MWT up to 6 months after intervention. These results were accompanied by an anticipated and acceptable risk profile. The relative increased incidence of device dislocation observed needs to be further elucidated.